Electrochemical detection of dopamine using arrays of liquid–liquid micro-interfaces created withinmicromachined silicon membranes - Berduque, A.; Zazpe, R.l; Arrigan, Damien (Elsevier BV, 2008)
The detection of protonated dopamine by differential pulse voltammetry (DPV) and square wave voltammetry (SWV) at arrays of micro-interfaces between two immiscible electrolyte solutions (ITIES) is presented. Microfabricated porous silicon membranes (consisting of eight pores, 26.6min radius and 500mpore–pore separation, in a hexagonal layout) were prepared by photolithographic and etching procedures. The membrane pores were fabricated with hydrophobic internal walls so that the organic phase filled the pores and created the liquid interface at the aqueous side of the membrane. These were used for harnessing the benefits of three-dimensional diffusion to the interface and for interface stabilisation.The liquid–liquid interface provides a simple method to overcome the major problem in the voltammetric detection of dopamine at solid electrodes due to the co-existence of ascorbate at higher concentrations. Selectivity for dopamine over ascorbatewas achieved by the use of dibenzo-18-crown-6 (DB18C6) for the facilitated ion transfer of dopamine across the ITIES array. Under these conditions, the presence of ascorbate in excess did not interfere in the detection of dopamine and the lowest concentration detectable was ca. 0.5M. In addition, the drawback of current signal saturation (non-linear increase of the peak current with the concentration of dopamine) observed at conventional (millimetre-sized) liquid–liquid interfaces was overcome using the microfabricated porous membranes